CAPITALIZATION LEVEL OF COMMERCIAL BANKS: THEORY AND PRACTICE - Mirzayev Mirza Abdullayevich (American Journals, 2024)
In the article, at the current stage of the liberalization and modernization of the economy in the Republic of Uzbekistan, the priority tasks of the banking system reform strategy are researched and the necessity, means, factors and effective measures of attracting private capital to the banking system are scientifically justified. In commercial banks, on the basis of capital attraction and improvement, it covers the need for monetary resources to carry out asset operations, primarily credit operations. Banks have limited opportunities to attract funds, and in all countries this process is regulated by the Central Bank. The borrowed funds make up the main part of the credit resources of commercial banks.
Keywords: Bank, private capital, banking system, strategy, level of bank, banking system resource, capitalization, finance.